Integrative genomic and single-cell framework identifies druggable targets for colorectal cancer precision therapy - Hong, Yanggang; Li, Jiajun; Xu, Nuo; Shu, Wanyi; Chen, Feng; Mi, Yuze; Geng, Haigang; Li, Qian (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) remains a leading cause of cancer-related mortality worldwide. Despite therapeutic advances, there is a critical need to identify novel, effective, and safe drug targets to improve precision treatment strategies.MethodsWe developed a multi-layered framework integrating Mendelian randomization (MR), colocalization analysis, genome-wide association study (GWAS) data, and expression quantitative trait loci (eQTLs) to prioritize causal and druggable genes in CRC. Single-cell and bulk RNA sequencing were used to characterize gene expression within the tumor microenvironment. Phenome-wide association studies (PheWAS) assessed off-target effects, and drug repurposing potential was evaluated using OpenTargets, DrugBank, and DGIdb. Validation of key targets was performed through RT-qPCR and immunohistochemistry (IHC) in CRC patient samples.ResultsOut of 4,479 druggable genes, MR analysis identified 47 candidates significantly associated with CRC risk. Six genes (TFRC, TNFSF14, LAMC1, PLK1, TYMS, and TSSK6) demonstrated strong colocalization signals and were further validated across replication datasets and subtype-stratified analyses. PheWAS analysis revealed minimal off-target effects for these genes. Notably, several of these genes have already been targeted by existing or investigational drugs, suggesting potential for repurposing. These genes exhibited distinct expression patterns in tumor and stromal cell types and were differentially expressed in CRC versus normal tissues. Among them, TNFSF14, an immune modulator, is particularly involved in regulating T cell activation within the tumor microenvironment.ConclusionThis study identifies and validates six promising druggable targets for CRC, providing a strong foundation for future preclinical studies. These findings open avenues for advancing precision oncology and drug repurposing strategies in CRC treatment, contributing to the development of more effective and personalized therapeutic approaches.